2010
DOI: 10.1051/epjconf/20100620001
|View full text |Cite
|
Sign up to set email alerts
|

Tensile behaviour of natural fibres. Effect of loading rate, temperature and humidity on the “accommodation” phenomena

Abstract: Abstract. The use of natural fibres in high performance composite requires an accurate understanding of the mechanical behaviour of the fibres themselves. As for all biobased materials, the mechanical properties of natural fibres depend generally on the testing rate and on the environmental conditions. In addition, natural fibres as hemp for example exhibit a particular mechanism of stiffness increase and accommodation phenomena under cyclic loading. Loading rate, temperature and humidity effects on the viscoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…4.b. This degree of stiffening is consistent with the experimental results obtained by the present authors with Repeated Progressive Loading (29,30), and is of the same order as that observed by Baley (6) and Silva (31), with flax and sisal fibres, respectively.…”
Section: Cellulose Microfibril Reorientation (Mfr)supporting
confidence: 93%
“…4.b. This degree of stiffening is consistent with the experimental results obtained by the present authors with Repeated Progressive Loading (29,30), and is of the same order as that observed by Baley (6) and Silva (31), with flax and sisal fibres, respectively.…”
Section: Cellulose Microfibril Reorientation (Mfr)supporting
confidence: 93%
“…6b shows that, below the yield point, the apparent Young's modulus increases by approximately 8% after 10 cycles at the same loading level. This stiffening phenomenon resulting from repeated low loading levels has been widely studied [25,26]; we showed that the rigidity increases by as much as 60% after a few thousand cycles, and tends to stabilize even when a higher number of cycles is applied. In this study, we show that when the yield point is exceeded, the fibre stiffness can be increased by almost 20% in a single cycle.…”
Section: Resultsmentioning
confidence: 71%